MODEL PENDIDIDKAN KARAKTER ANAK DALAM PERSPEKTIF IBNU QAYYIM AL-JAUZIYAH - Zaini (LP2M Universitas PTIQ Jakarta, 2025)
This study aims to analyze the model of children’s character education from the perspective of Ibnu Qayyim Al-Jauziyah and its relevance to contemporary character education. The study focuses on the concepts of tawhid, role modeling, habituation, self-control, and environmental supervision as the foundation for children’s character building. This research employs a library research method with a qualitative approach. The data were collected through documentation studies from the works of Ibnu Qayyim Al-Jauziyah, scientific journals, Islamic education books, and other relevant academic sources. The data analysis technique used content analysis through the stages of data reduction, data presentation, and conclusion drawing. The findings reveal that the character education model according to Ibnu Qayyim Al-Jauziyah places tawhid as the primary foundation for shaping children’s morals and personality. Character education is implemented through parental and teacher role modeling, habituation of positive behavior, spiritual development, and supervision of children’s social environments. This educational model is highly relevant to modern educational needs because it integrates intellectual, emotional, social, and spiritual aspects in shaping the character of the younger generation. Therefore, the concept of character education proposed by Ibnu Qayyim Al-Jauziyah can serve as an alternative holistic and contextual Islamic educational model.